Full Citizens, Double Agents: An Agent-Centred Account of Dual Citizenship - Peruniak, Blair (Université Saint-Paul / Saint Paul University, 2013)
Dual citizenship—once synonymous with a dubious moral and political status—has recently been hailed as a new standard of autonomy, inclusiveness, and political choice. The growing recognition of multiple citizenship as a viable, constitutionally protected status has been viewed as an indication of states’ increasing willingness to relinquish controls over personal identity-formation and conceptions of political belonging. However, vastly divergent views about the nature and influence of plural citizenship persist, hampering efforts to assess its significance as a progressive and democratic political phenomenon. The thesis highlights the normative implications of dual citizenship as a moral-political issue from the perspective of the theory of moral agency. Drawing from the work of Christine Korsgaard, I argue that dual citizenship is not a practical identity that individuals can endorse as autonomous, self-respecting moral agents. Nonetheless, dual citizenship represents a valuable political ideal for persons whose interest in avoiding compromises to their moral agency entails the capacity for critical self-reflection on state membership. The thesis contributes to current developments in transnational citizenship theory while underscoring the importance of the theory of moral agency for understanding of the value of citizenship.
Keywords: dual citizenship